Residential radon exposure and esophageal cancer. An ecological study from an area with high indoor radon concentration (Galicia, Spain). (April 2014) - Ruano-Ravina, Alberto; Aragonés, Nuria; Pérez-Ríos, Mónica; López-Abente, Gonzalo; Barros-Dios, Juan M.
Abstract Purpose: To analyze the correlation between municipal esophageal cancer relative risk and municipal residential radon concentration in a high radon emission Spanish area. Materials and methods: We performed an ecological study at municipal level in Galicia, Spain. For each municipality we estimated the median radon concentration and the relative risk (RR) for esophageal cancer mortality for males and females. The relative risk was calculated using a Bayesian approach. Homes with data on radon concentration were selected through stratified random sampling. To be included, each municipality had to have at least five radon measurements. We obtained Spearman's correlations for median residential radon concentration and esophageal cancer mortality RR for males and females, separately. Results: We included 129 municipalities, covering the 79% of Galician population. 14% of municipalities had radon concentrations above the United States Environmental Protection Agency (USEPA) action level. We found a statistically significant correlation among residential radon and esophageal cancer mortality RR for males (p < 0.001), but not for females. When the analysis was restricted to municipalities with more than 15 radon measurements the correlation pattern remained. Conclusions: This is the first study analyzing the association between residential radon and esophageal cancer. The results suggesting a possible effect of residential radon on esophageal cancer mortality should be explored through more robust epidemiological designs such as case-control studies.